2020
DOI: 10.1007/s11882-020-00972-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Utility of Olfactory Dysfunction in COVID-19: a Systematic Review and Meta-analysis

Abstract: Background Olfactory dysfunction (OD) has been gaining recognition as a symptom of COVID-19, but its clinical utility has not been well defined. Objectives To quantify the clinical utility of identifying OD in the diagnosis of COVID-19 and determine an estimate of the frequency of OD amongst these patients. Methods PubMed was searched up to 1 August 2020. Meta-analysis A included studies if they compared the frequency of OD in COVID-19 positive patients (proven by reverse transcription polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
69
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 94 publications
13
69
1
1
Order By: Relevance
“…Our results showed that the olfactory test specificity to detect OD in patients infected with COVID-19 was very high (∼95%), which is consistent with other reports 23 including by the CDC 24 indicating that “a new loss of taste or smell” is the single best indicator symptom of COVID-19, as based on the odds ratio. Although OD is acknowledged by many research teams and listed on the WHO website as a finding consistent with SARS-CoV-2 infection, little attention is given that OD is a better indicator of COVID-19 than other symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that the olfactory test specificity to detect OD in patients infected with COVID-19 was very high (∼95%), which is consistent with other reports 23 including by the CDC 24 indicating that “a new loss of taste or smell” is the single best indicator symptom of COVID-19, as based on the odds ratio. Although OD is acknowledged by many research teams and listed on the WHO website as a finding consistent with SARS-CoV-2 infection, little attention is given that OD is a better indicator of COVID-19 than other symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent regarding some factors associated with a greater probability of positivity to COVID-19, for example, the symptoms described such as anosmia or respiratory distress, in the context of the pandemic, have a strong disease predictive association. 25 In recent systematic reviews and meta-analyses, anosmia has been similarly associated with COVID-19 infection with an OR between 11 and 14, 26,27 like in our study. These findings could be overestimated as the prevalence of our outcome was high (> 20%), but when correcting the analyzes using Prevalence Ratios (PR) for smell/taste alteration, the PR was 2·74 (2·41-3·12), a significant association but with lower point estimates.…”
Section: Discussionsupporting
confidence: 85%
“…Although SARS-Cov-2 accesses the respiratory system with most people experiencing a mild or subclinical disease, especially in the early stages, clinical manifestations of COVID-19 are broad and include common symptoms such as malaise, fever, cough, shortness of breath, myalgia, sore throat, headache, nausea, or diarrhea [ 1 , 2 ]. Nevertheless, loss of smell and taste have emerged as the most prevalent and predictive symptoms in mild COVID-19 cases [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%